Semitendinosus and biceps femoris long head active stiffness response until failure in professional footballers with vs. without previous hamstring injury - Freitas, S. R.; Mendes, B.; Firmino, T.; Correia, J. P.; Witvrouw, E. M. C.; Oliveira, E. R.; Vaz, J. R. (European Journal of Sport Science, 2022)
This study sought to examine the active stiffness of semitendinosus (ST) and biceps femoris long head (BFlh) during a knee flexor isometric contraction at 20% of maximal voluntary isometric contraction until failure in elite footballers (n=50, age: 22.3±5.3 years; height: 1.82±0.08 m; body mass: 74.7±9.0 kg). Active stiffness was assessed using ultrasound-based shear wave elastography by means of shear modulus quantification. Comparisons were performed between limbs with (n=11) vs. without (n=89) previous hamstring injury. Similar time until failure in the knee flexor fatigue task was observed between groups (p=0.401). At the start of the task, lower limbs with previous hamstring injury showed a lower BFlh active stiffness (31.0.1±10.4 kPa, p=0.023) and BFlh/ST active stiffness ratio (0.50±0.29), and no differences for ST (72.8±26.8 kPa, p=0.221) compared to lower limbs without previous hamstring injuries (BFlh: 38.0±9.6 kPa; ST: 64.0±18.4 kPa; BFlh/ST: 0.65±0.27). During the task, the ST active stiffness in both groups decreased from 80% of task time (p=0.032), in the absence of changes in BFlh active stiffness (p=0.534), resulting in an increase in BFlh/ST active stiffness from 80% of task time (p=0.029). No differences between limbs were observed during the fatigue task for all parameters (p>0.099). Future research is warranted to verify if the differences found represent an increased risk of hamstring injury.